THE ROLE OF DIGITAL MARKETING AND SOCIAL MEDIA STRATEGIES IN THE DEVELOPMENT OF THE CULINARY BUSINESS FOR YOUNG BUSINESS LEADERS - Hasugian, Buyung Solihin; Indallah, Tara Wardha (Universitas Dharmawangsa Medan, 2022)
ABSTRACTThe use of social media for business development is not a new concept for business owners. Despite this, there are many people who work in the food industry on a small scale who benefit from social media. Many others are among those who have used social media but have experienced difficulties in using it. This study investigates the impact of social media on the growth of small businesses, particularly in the food industry, based on the opinions of those who have used it. Using a quantitative method with a focus on psychology, the findings indicate that social media use can significantly aid in the growth of businesses. In order for technology to be used to its full potential, businesses must continue to invest in social media growth. In the long run, social media is not the most important factor in increasing sales. Good product and service development is a key factor in achieving faster sales growth. The results of this study may be extended in order to obtain more precise results as a single theory of microeconomic development.Â Keywords : Â Influence of Social Media, Promotion, Marketing, Consumer Decisions